2016
DOI: 10.18632/aging.101066
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity Related Gene 3 (PRG3) overcomes myelin-associated growth inhibition and promotes functional recovery after spinal cord injury

Abstract: The Plasticity Related Gene family covers five, brain-specific, transmembrane proteins (PRG1-5, also termed LPPR1-5) that operate in neuronal plasticity during development, aging and brain trauma. Here we investigated the role of the PRG family on axonal and filopodia outgrowth. Comparative analysis revealed the strongest outgrowth induced by PRG3 (LPPR1). During development, PRG3 is ubiquitously located at the tip of neuronal processes and at the plasma membrane and declines with age. In utero electroporation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(54 citation statements)
references
References 56 publications
5
49
0
Order By: Relevance
“…Studies in mice have shown that after neuronal injury, overexpression of LPPR1 enhances axonal growth, improves motor behavior, and promotes functional recovery. 33 , 34 Extrapolating to our findings, we propose that LPPR1 is involved, not necessarily in the cause of PD, rather in response to damage, and influences the efficacy of regeneration and the subsequent rate of deterioration in preclinical PD. The actual cause of injury and neuronal death is not stipulated in this hypothesis; it could be head trauma, environmental toxins or genetic, but once the initial damage is incurred, it is the efficacy of intrinsic mechanisms of repair that determine the rate of disease progression.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Studies in mice have shown that after neuronal injury, overexpression of LPPR1 enhances axonal growth, improves motor behavior, and promotes functional recovery. 33 , 34 Extrapolating to our findings, we propose that LPPR1 is involved, not necessarily in the cause of PD, rather in response to damage, and influences the efficacy of regeneration and the subsequent rate of deterioration in preclinical PD. The actual cause of injury and neuronal death is not stipulated in this hypothesis; it could be head trauma, environmental toxins or genetic, but once the initial damage is incurred, it is the efficacy of intrinsic mechanisms of repair that determine the rate of disease progression.…”
Section: Discussionsupporting
confidence: 75%
“…PAGE I participants being significantly older than NGRC and PAGE P participants may also be a factor. LPPR1 promotes neuroregeneration, 32 34 but its expression diminishes with age to nearly undetectable level by age 40 years ( figure 2C ). One can speculate that some detrimental variants may not have an effect after a certain age when the gene is no longer expressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 In brief, following 20 min incubation on ice, samples were centrifuged at 8000 r.p.m for 10 min. Supernatants were isolated and protein concentration measured with the NanoVue Plus Spectrophotometer (GE Healthcare, UK).…”
Section: Methodsmentioning
confidence: 99%
“…Another study in a model of incomplete SCI reported that neurotrophic upregulation demonstrated an injury-specific BDNF response including regenerative sprouting and increased connectivity of injured neurons with propriospinal interneurons [ 6 ]. Other promising targets include the PRG3 gene, which induces filopodia formation and axonal growth and has also been shown to overcome a range of neurite growth inhibitors, though not yet evaluated in SCI specifically [ 7 ].…”
Section: Introductionmentioning
confidence: 99%